Levels of Organochlorine Insecticide Residues in Fresh Tomatoes from some Selected Farming Communities in Navrongo, Ghana - Nunifant Konlan, Timothy (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science in Environmental Science